Optimization of lipid extraction from the oleaginous yeasts Rhodotorula glutinis and Lipomyces kononenkoae - Vasconcelos, Bruno Neto (2018)
The constant growing demand for vegetable oil for biodiesel and food is raising many environmental concerns about the sustainability of its production based on crops. Oleaginous yeasts show great potential to end with those concerns due to their high lipid productivity in small areas. To evaluate their productivity in lipids, an efficient and reproducible extraction process should be used. As no standard extraction process is available for the extraction of yeast lipids, an optimized extraction process is presented. In this work, the lipids extraction process for the yeasts Rhodotorula glutinis and Lipomyces kononenkoae is optimized using bead beating for cell rupture and introducing adaptations of the two most used extraction methods (Bligh and Dyer and Folch). For Rhodotorula g. the optimum extraction conditions are obtained by the Bligh and Dyer method applying 4.8 cycles of 47 s with 0.7 g of glass beads. For Lipomyces k. the optimum extraction conditions make use of the Folch method applying seven cycles of 42 s with 0.54 g of glass beads. These results reinforce the idea that, for each yeast, different extraction processes may be needed to correctly determine the lipid yield. The extraction procedure was further evaluated with less harmful solvents. Toluene was tested as a possible substitute of chloroform, and ethanol as a possible substitute of methanol. With the optimized extraction process, better results for Lipomyces k. were obtained using toluene and ethanol, while for Rhodotorula g. toluene proved to be a valid substitute of chloroform but ethanol is far less effective than methanol.